Alport Syndrome Presenting as Incidental Finding of Proteinuria on Pre-Employment Checkup: A Case Report - Abigayle Therese R. Guiritan; Lee-Boyd D. Valencia; Sonia L. Chicano (Case Reports in Nephrology)
Conclusion: Although a rare cause of glomerulonephritis, Alport syndrome must be considered in patients presenting with subnephrotic range proteinuria and microscopic hematuria. Thorough history and physical examination and characteristic findings on kidney biopsy can help in the prompt diagnosis of the disease. Multidisciplinary care and early intervention can improve the quality of life and delay the progression to end-stage kidney disease among these patients.